English linguistic knowledge of police trainees in SAPS training academies - Tebogo Johannes Kekana; Malesela Edward Montle (EduLite: Journal of English Education, Literature and Culture, 2022)
This article reports on the findings of a study about South African Police Services (SAPS) training with specific reference to English linguistic knowledge of police trainees. English linguistic training in (SAPS) training academies have become central to both training and teaching and learning. Despite several benefits identified in literature regarding adequate English linguistic knowledge, the training in SAPS leaves much to be desired. Therefore, the impetus of this paper is to make a case to challenge the tacit and poignant factors affecting effective SAPS training program with specific reference to English linguistic competence. The researcher makes a case that the training program in its current state is faced with many challenges and intricacies that hampers it from achieving one of its goals which is to produce police officers with adequate workplace English linguistic competency. A mixed research approach was adopted to investigate the phenomena. The research instruments were a locally designed questionnaire complimented by in-depth interviews with a selected sample and extensive literature review of scholarly literature on the matter. Needs Analysis theory was adopted as the pillar in this study. Among the findings was the lack of expertise in teaching English writing by police instructors. The study also found that SAPS Language policy is ‘completely’ silent as far as pedagogy is concerned in SAPS training academies. The study also found the other a systemic problem called ‘placement conundrum’. Furthermore, the study also found that ineffective English writing screening measures for police recruits contributes to the problem. In addition, the other unsurprising was the over dominance of physical training over academic teaching in the training colleges. This study underscores the crucial aspect of reflective research as a source of information for improving training in SAPS training academies.